Perspectives on the Militarization of Public Security in Contemporary Brazil - Francisco de Souza, Luis Antonio [UNESP]; Aguiar Serra, Carlos Henrique; Battibugli, Thais (Onati Int Inst Sociology Law, 2019)
Brazil still has not fully accomplished procedural democracy, despite being a formal democracy funded on a federal constitution and on an organized judicial system. The country has not been able to foster the principles of justice, peace, development, and equity for most of the population, and the state apparatus is restricted regarding social control, transparency, and effectiveness of public policies. This scenario resulted in the rise of violence, criminality, organized crime, and urban disorder, which has led to the militarization of public security both with the improvement of the military police's structure and with the presence of the armed forces performing public security activities. This process of militarization has increased in the last two years, and for the first time since 1985, the military managed to ascend to the most powerful positions in the Brazilian government. This article discusses the militarization of public security in Brazil, pointing to the risks of a new and enduring process of militarization of Brazilian society, which still suffers from limited rights and lack of constitutional guarantees.
Keywords: Public security; police; police violence; militarization